Synthesizing enzymes for four neuroactive substances in motor neurons and neuromuscular junctions: light and electron microscopic immunocytochemistry. - Chan-Palay, V (1982)
Immunocytochemical evidence is presented for the existence of choline acetyltransferase (ChoAcTase), cysteine sulfinic acid decarboxylase (CSADCase), tyrosine hydroxylase (TyrOHase), and glutamic acid decarboxylase (GluDCase) in large motor neurons of the hypoglossal nucleus and the spinal cord and in nerve terminals of motor end plates in tongue and skeletal muscle of five mammalian species, including man. These enzymes, which are responsible for the synthesis of acetylcholine (AcCho), taurine, dopamine, and gamma-aminobutyrate (GABA), respectively, were detected by immunocytochemical studies with monoclonal or polyclonal antibodies raised against the enzymes. Electron microscopy of the neuromuscular junctions showed that the immunoreactivity in each case was confined to the cytoplasmic matrix of presynaptic nerve terminals. Immunoreactivity obtained for each enzyme antibody varied with the species. It was highest in fresh, unfixed muscle and lowest in aldehyde-fixed specimens. Negative controls were obtained with preimmune sera and antisera preabsorbed with pure ChoAcTase, CSADCase, or GluDCase antigen. Double-labeling studies with ChoAcTase antibodies and acetylcholinesterase (AcChoEase) antibodies, AcChoEase enzyme activity, or alpha-bungarotoxin binding indicated that ChoAcTase, AcChoEase, and AcCho receptors were colocalized at the same end plates.